A Computational Study of Hydrodynamic Interactions Between Pairs of Sperm With Planar and Quasi-Planar Beat Forms - Carichino, Lucia; Drumm, Derek; Olson, Sarah D. (Frontiers in Physics, 2021)
Although hydrodynamic interactions and cooperative swimming of mammalian sperm are observed, the key factors that lead to attraction or repulsion in different confined geometries are not well understood. In this study, we simulate the 3-dimensional fluid-structure interaction of pairs of swimmers utilizing the Method of Regularized Stokeslets, accounting for a nearby wall via a regularized image system. To investigate emergent trajectories of swimmers, we look at different preferred beat forms (planar or quasi-planar) and initializations of swimmers in different beat planes (co-planar or centerlines in parallel planes). We observe forward progression of swimmers in free space with stable attraction of swimmers with quasi-planar beat forms as well as swimmers with planar beat forms that are co-planar. In contrast, for swimmers initialized in parallel beat planes with a planar beat form, we observe alternating periods of attraction and repulsion. When the pairs of swimmers are perpendicular to a nearby wall, for all cases considered, they exhibit a stable attraction to the wall and reach a stable distance between swimmers. Interestingly, we observe sperm rolling in the case of swimmers with preferred planar beat forms that are initialized in parallel beat planes and near a wall.